Association Between Annual Surgeon Total Thyroidectomy Volume and Transient and Permanent Complications - Muhammad Haikal, Muhammad Haikal; Tri Teguh, Tri Teguh (International Medical Journal Corp. Ltd, 2024)
Background: The association between annual surgeon total thyroidectomy volume and the incidence of transient and permanent complications has been a focal point of research in recent years, reflecting the critical importance of surgical expertise in determining patient outcomes. The literature presents a nuanced perspective on this relationship, highlighting various dimensions of surgeon experience, procedural safety, and complication rates. Literature Review: The reviewed literature collectively underscores the significant association between a surgeon's annual total thyroidectomy volume and the rates of transient and permanent complications. The studies analyzed highlight the complexity of surgical outcomes, emphasizing that higher surgical volumes are consistently linked to improved patient outcomes, particularly in terms of complication rates. Conclusion: In conclusion, the body of literature reviewed presents compelling evidence that higher annual surgeon total thyroidectomy volume is associated with reduced rates of both transient and permanent complications. This relationship not only highlights the importance of surgical expertise but also suggests that institutional practices should prioritize the development and maintenance of high-volume surgical teams to enhance patient safety and surgical effectiveness.